Spatiotemporal Variations of Ecosystem Service Indicators and the Driving Factors Under Climate Change in the Qinghai–Tibet Highway Corridor - Yang, Siqi; Zhu, Gaoru; Zhang, Lixiao; Xu, Honglei; Cheng, Jinxiang (Frontiers in Environmental Science, 2022)
In recent decades, the influence of climate change and human activities on the ecosystem structure and function in the Qinghai-Tibet Plateau (QTP) has been extensively studied. However, few studies focus on linear traffic corridor area, which is heavily affected by human activities. Taking the Golmud-Lhasa national highway corridor as a case, this study investigated the land use and land cover change (LUCC) and spatio-temporal variations of ecosystem status by using ecosystem indices of fractional vegetation cover (FVC), leaf area index (LAI), evapotranspiration (ET), and net primary productivity (NPP) from 2000 to 2020. The results showed that LUCC was faster in the last decade, mostly characterized by the conversion from grassland to unused land. In buffer within 3000m, the proportions of productive areas represented the increased trends with distance. In terms of ecosystem change, the improved areas outweighed the degraded areas in FVC, LAI, and NPP from 2000 to 2020, mostly positioned in Qinghai Province. FVC, LAI and NPP peaked at about 6000m over time. With regard to influence factors, precipitation (20.46%) and temperature (14.08%) both positively influenced FVC spatio-temporal variation. Nearly 60% of the area showed an increased NPP over time, especially in Qinghai Province, which could attribute to the temperature increase over the last two decades. In addition, the effects of meteorological factors on ecosystem indices exhibit a distance-decay trend, in which the positive effect of temperature on NPP decreased with distance. The findings of this study could provide a reference for the ecological recovery of traffic corridors in alpine fragile areas.